Nutritional assessment and serum zinc and copper concentration in leukemic children - Sgarbieri, Ursula Rohr; Fisberg, Mauro; Tone, Luis Gonzaga (São Paulo Medical Journal, 1999)
CONTEXT: Malnutrition in childhood cancer is commonly a serious problem. Changes in blood zinc and copper have also been found in malignant diseases. OBJECTIVE: To describe the protein-energy nutritional status and serum zinc and copper of children with newly diagnosed leukemia. DESIGN: Cross-sectional study. SETTING: University referral center. PARTICIPANTS: 23 children with newly diagnosed acute lymphocytic leukemia (ALL) or acute non-lymphocytic leukemia (ANLL) between the ages of 1and 10 years. The control subjects were 31 healthy school children of similar age from local schools. MAIN MEASURES: Anthropometric measurements of height/age and weight/height, food intake and serum levels of zinc and copper. RESULTS: Almost the entire group of children were eutrophic. Zinc and copper intake were below the recommended values. Serum zinc levels were significantly lower and serum copper levels were significantly higher in the leukemic group when compared to normal children. CONCLUSION: At the time of diagnosis the children suffering from leukemia were not overtly malnourished but blood analysis showed alterations in concentrations of the trace elements zinc and copper.